The National Student Survey: validation in Portuguese medical students. Issue 1 (2nd January 2019) - Martins, Maria João; Reis Marques, Tiago; Laíns, Inês; Leal, Inês; Pessanha, Inês; Brochado, Bruno; Oliveira Santos, Manuel; Pinto Teixeira, Pedro; Fernandes, Diogo Hipólito; Silva, João Carlos; Sampaio, Filipa Almeida; Brandão, Mariana; et al.
Abstract: The UK National Student Survey (NSS) is a sound and widely used instrument for assessing students' academic experiences. We aimed to translate the NSS for Portuguese students and to validate the instrument in a sample of medical undergraduates. The research team translated and adapted the NSS for Portuguese students (NSS-P). The survey was administered on an online platform to 1, 256 final-year students at eight Portuguese medical schools. A total of 329 medical students (69.9% female) replied to the NSS-P, a response rate of 26.2%. Confirmatory factor analysis showed that the original six-factor structure had an adequate fit to the data. Adequate internal consistency was observed for all the subscales. Medium to large correlations were found among all the subscale scores and between the subscale scores and the students' overall satisfaction. Multiple regression showed that the scores on the Teaching, Organization and Management and Personal Development subscales significantly predicted the students' overall satisfaction. Approximately 64% of the students reported being satisfied with the quality of their courses. Significant differences among the medical schools in their NSS-P scores were found. The NSS-P is a valid and reliable measure for assessing medical students' perceptions of academic quality.